IMPLEMENTASI PERPRES NO.13 TAHUN 2018 SEBAGAI STRATEGI PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG DI KORPORASI - Zhafirah Nisa Almira; Keiza Aurora Karenina; Thereza Hilya Hutasoit; Hawila Winona Lakusa; Dela Ulianda Simanjuntak (Jurnal Hukum Statuta, 2022)
Indonesia as one of the developing countries that focuses on the development of the economy to the private sector, which is now dominated by corporations. In fact, many corporations commit money laundering crimes so that the origin of these assets is difficult to trace by law enforcement officers and there are many other factors that can cause money laundering by corporations. The rise of money laundering in corporations is something that the government must address. Where these incidents need to be handled with strategies that can work effectively. The presence of Presidential Decree 13 of 2018 can be an effort to overcome and eradicate money laundering crimes in corporations. The type of research used is normative juridical. This research is a literature research with a statutory and conceptual approach. It is known that there are several problems in the handling of money laundering which resulted in its implementation not being able to run effectively. The presence of Presidential Decree 13 of 2018 concerning the Application of the Principle of Recognizing the Beneficial Owner of a Corporation in the Context of Prevention and Eradication of the Crime of Money Laundering and the Financing of Terrorism. Where it requires transparency in its implementation and is supported by technical rules that have been issued, namely Ministry of Law and Human Rights Regulation No. 15 of 2019 about Procedures for Implementing the Implementation of the Principles of Recognizing the Beneficial Owners of Corporations and Ministry of Law and Human Rights Regulation No. 21 of 2019 concerning Procedures for Supervision of the Implementation of the Principle of Recognizing the Beneficial Owners of Corporations. Then the application of beneficial ownership will be effective, measurable, up-to-date, so that it can prevent and eradicate money laundering offenses in corporations.